Trabalho e a dupla invisibilidade das mulheres catadoras das associações de materiais recicláveis de Ponta Grossa-PR na pandemia da Covid-19 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This research is based on an analysis of the reality of women waste pickers during the Covid-19 pandemic, since it has brought changes to the daily lives of society as a whole. In this thesis, the general objective was to understand the changes in the reality of women waste pickers in the city of Ponta Grossa - PR from the Covid-19 pandemic in the years 2020 to 2024. This time frame was chosen because the research sought to understand this process during and after the Covid-19 pandemic. In addition, the specific objectives were: a) to identify the impacts of the pandemic on the structures of the waste pickers' associations in Ponta Grossa; b) to map the profile of the participants in the associations during and after the pandemic; c) to understand how the daily life of the women waste pickers participating in the associations in Ponta Grossa was in their family organization during the pandemic; d) to analyse the self-perception of the women waste pickers about the work they do, especially after the pandemic. For the purposes of this thesis, a qualitative, interdisciplinary study was carried out, using historical-dialectical materialism. The methodological procedures used were bibliographical, documentary and field research, the latter involving a questionnaire with all the members of the waste pickers' associations and, finally, semi-structured interviews with the selected sample of women waste pickers. After the data collection phase of the research, the data was analyzed using “R” software and content analysis. The thesis is that there is a need for effective public policies to recognize the double invisibility that the universe of women waste pickers experiences in their daily lives, since it was possible to understand from the speeches and observations made during the field research that these women suffer intense inequalities and depend mostly on other women to carry out the invisible jobs that are present in their routines. In this way, it is understood that, although the pandemic has been challenging for society as a whole, for the waste pickers it has been the catalyst that has generated a mixture of feelings as they have realized with greater emphasis the importance of their work in society, both as women and as waste pickers. Consequently, it became clear that there is an urgent need for concrete action, through public policies that recognize and value the doubly invisible work they do.
Keywords: Catadoras; Trabalho invisível; Teoria da Reprodução Social; Women Waste Pickers; Invisible Work; Social Reproduction Theory; CNPQ::CIENCIAS SOCIAIS APLICADAS